Mild and efficient C2-alkenylation of indoles with alkynes catalyzed by a cobalt complex - Ding, Zhenhua (2013)
Direct alkenylation of the C2-position of indoles bearing an easily removable N-pyrimidyl group with alkynes has been achieved by using a cobalt catalyst complexed with a phosphine–pyridine bidentate ligand. This reaction has wide substrate scope and is highly efficient and stereoselective at room temperature. The alkenylated indoles serve as useful platforms for further synthetic transformations (some products of these transformations are shown in the scheme).